2013
DOI: 10.1139/cjb-2013-0021
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen uptake during the leafless period in juvenile plants of a winter-green perennial herb, Lycoris radiata var. radiata (Amaryllidaceae)

Abstract: Leafless plants are often assumed to be in a dormant stage with low physiological activity. However, having an ability to take up nutrients during the leafless period may be beneficial if nutrient availability is high during that period. We examined a winter-green geophyte, Lycoris radiata var. radiata, to determine whether it maintained root activity during the leafless period for this species (from June to September in central Japan). The species had roots throughout the year, but new roots emerged mainly du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The development of new secondary roots (fine roots) was most rapid during the autumn (November-December) (Cai et al, 2018a). This was consistent with a previous observation that old L. radiata roots were replaced with new roots in April (Nishitani et al, 2013).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The development of new secondary roots (fine roots) was most rapid during the autumn (November-December) (Cai et al, 2018a). This was consistent with a previous observation that old L. radiata roots were replaced with new roots in April (Nishitani et al, 2013).…”
Section: Resultssupporting
confidence: 93%
“…The unique seasonal separation of vegetative growth and reproductive growth in this species (i.e., summer dormancy) is largely associated with the shaded native habitat of this plant: inside temperate broad-leaved forests (Abdusalam et al, 2012;Kawano, 2009). Indeed, moderate shade (30%-65%) improves the yield and quality of cultivated L. radiata flowers Nishitani et al, 2013). Net photosynthetic rate and flower quality are optimal in L. radiata under 45% shade (Cai et al, 2013(Cai et al, , 2018b.…”
Section: Discussionmentioning
confidence: 99%
“…In another study of a subarctic heath system, Larsen et al (2012) used an 15 N-labeled glycine tracer and detected that graminoids, evergreen dwarf shrubs, and mosses were able to take up nitrogen during late winter and early spring, although with different temporal patterns. Nishitani et al (2013) observed that a juvenile winter-green perennial herb actively took up nitrogen during its leafless period. Together, these observations confirm that plant root nutrient acquisition and photosynthesis can occur independently and that, like microbes (e.g., Ji et al 2015), plants maintain flexible nutrient stoichiometry.…”
Section: Observations Revealing Photosynthesis-independent Plant Root Nutrient Acquisitionmentioning
confidence: 99%
“…This species is also cultivated as a garden plant. The plants have green leaves from autumn to spring, with maximum photosynthetic capacity during winter, and their roots are maintained and absorb N even during the leafless summer [25]. To investigate the functional differences in seasonally absorbed N, we designed experiments such that each plant could access soil N during only one or two of three fertilizer supply periods: summer (leafless period), autumn ( period of leaf flush) and winter ( period of active growth with fully developed foliage).…”
mentioning
confidence: 99%